Pulmonary artery pressure increases during commercial air travel in healthy passengers. - Smith, T; Talbot, N; Chang, R; Wilkinson, E; Nickol, A; Newman, D; Robbins, P; Dorrington, K (2012)
BACKGROUND: It is not known whether the mild hypoxia experienced by passengers during commercial air travel triggers hypoxic pulmonary vasoconstriction and increases pulmonary artery pressure in flight. Insidious pulmonary hypertensive responses could endanger susceptible passengers who have cardiopulmonary disease or increased hypoxic pulmonary vascular sensitivity. Understanding these effects may improve pre-flight assessment of fitness-to-fly and reduce in-flight morbidity and mortality. METHODS: Eight healthy volunteers were studied during a scheduled commercial airline flight from London, UK, to Denver, CO. The aircraft was a Boeing 777 and the duration of the flight was 9 h. Systolic pulmonary artery pressure (sPAP) was assessed by portable Doppler echocardiography during the flight and over the following week in Denver, where the altitude (5280 ft/1610 m) simulates a commercial airliner environment. RESULTS: Cruising cabin altitude ranged between 5840 and 7170 ft (1780 to 2185 m), and mean arterial oxygen saturation was 95 +/- 0.6% during the flight. Mean sPAP increased significantly in flight by 6 +/- 1 mmHg to 33 +/- 1 mmHg, an increase of approximately 20%. After landing in Denver, sPAP was still 3 +/- 1 mmHg higher than baseline and remained elevated at 30 +/- 1 mmHg for a further 12 h. CONCLUSIONS: Pulmonary artery pressure increases during commercial air travel in healthy passengers, raising the possibility that hypoxic pulmonary hypertension could develop in susceptible individuals. A hypoxia altitude simulation test with simultaneous echocardiography ('HAST-echo') may be beneficial in assessing fitness to fly in vulnerable patients.